2017
DOI: 10.4292/wjgpt.v8.i2.131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of infliximab one-hour infusion protocol in patients with inflammatory bowel diseases: A multicenter study

Abstract: AIMTo assess the impact of short infliximab (IFX) infusion on hospital resource utilization and costs.METHODSAll inflammatory bowel diseases (IBD) patients who received IFX 1 h infusion from March 2007 to September 2014 in eight centers from Southern Italy were included in the analysis. Demographic, clinical and infusion related data were collected. The potential benefits related to the short infusion protocol were assessed both in terms of time saving and increased infusion unit capacity. In addition, indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…A number of studies have demonstrated that rapid infusions (≤ 60 min) of reference infliximab are not associated with an increased risk of infusion reactions 5–7 . Shorter infusion administration times provide cost‐saving opportunities for centres by increasing the number of available appointments, and may improve patient experience by reducing the amount of time spent at the facility 8 . Increased use of biosimilar infliximab provides potential cost‐savings for institutions as well 9 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that rapid infusions (≤ 60 min) of reference infliximab are not associated with an increased risk of infusion reactions 5–7 . Shorter infusion administration times provide cost‐saving opportunities for centres by increasing the number of available appointments, and may improve patient experience by reducing the amount of time spent at the facility 8 . Increased use of biosimilar infliximab provides potential cost‐savings for institutions as well 9 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“… 5 , 6 , 7 Shorter infusion administration times provide cost‐saving opportunities for centres by increasing the number of available appointments, and may improve patient experience by reducing the amount of time spent at the facility. 8 Increased use of biosimilar infliximab provides potential cost‐savings for institutions as well. 9 The safety of rapid infusions for infliximab biosimilar agents is largely unknown, and further assessment of rapid infliximab biosimilar infusions is needed to determine the safety of this practice.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…[10][11][12] Furthermore, accelerated infliximab infusions have been shown to reduce significantly nursing time, healthcare resources, and increase patient satisfaction. [13][14][15][16] Given the safety and benefits of accelerated infliximab infusion protocol, our IBD center developed a quality improvement (QI) project to shorten the average time spent at the outpatient biologics infusion center. The primary aim of this QI project was to reduce by 40%, both the average infliximab infusion time and the total time spent at the outpatient biologics infusion center.…”
Section: Introductionmentioning
confidence: 99%
“…Short infusion (over 30–60 min) protocols have been found safe in patients with rheumatoid arthritis and IBD 10–12 . Furthermore, accelerated infliximab infusions have been shown to reduce significantly nursing time, healthcare resources, and increase patient satisfaction 13–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation